Effects of different cropping systems and weed management methods on free energy and content of pigments in maize (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2014)
Rotation is a cropping system that has many advantages and ensures better crop growth and yielding. Its combinination with other cropping measures can ensure optimal crop density for maximal growth and photosynthesis efficiency. The aim of this study was to investigate the influence of different cropping systems: monoculture and two rotations, including maize, wheat and soybean (MSW and MWS), and different weed management methods (weed removal by hoeing, application of a full recommended herbicide dose (RD) and half that dose (0.5 RD), and weedy check) on weed biomass and maize growth parameters - leaf area index (LAI), free energy, contents of chlorophyll and carotenoids, grain yield, and their possible relationships in two fields of the maize hybrids ZP 677 (H1) and ZP 606 (H2).The lowest LAI and grain yield were found in monoculture, particularly in weedy check, which had relatively high weed infestation. Higher weed biomass was also observed in herbicide treated plots in monoculture. Such high competition pressure indicates a stress reflected on reduced LAI and chlorophyll content, and increased free energy and content of carotenoids. On the other hand, rotation, particularly if it is combined with the  application of herbicides or hoeing, had a positive impact on yielding potential by increasing LAI and the contents of chlorophyll and carotenoids, and decreasing free energy.
Keywords: Weeds; Maize; Herbicides; Energy; Cropping systems; Chlorophylls; Carotenoids